International Monetary Fund Annual Report 2007 : Financial Statements. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 2007)
The 2007 Annual Report to the Board of Governors reviews the IMF's activities and policies during the financial year (May 1, 2006, through April 30, 2007). The financial statements of the IMF for FY2007 are available on the CD-ROM accompanying the print report. Print copies of the financial statements are also available as a stand-alone item.